Synthesis of 2-(Substituted Benzylidene)-7- Substituted-5-Chloro Coumaran-3-One - Kolhe, S.V.; Doshi, A.G.; Raut, A.W. (Asian Journal of Chemistry, 2010)
2-Hydroxy substituted chalcone (la-p) was dissolved in DMSO and mercuric acetate was added to it. The reaction mixture was refluxed for 2-3 h and then diluted with water. The solid separated was crystallized from rectified spirit to give coumaran-3-ones (IIa–p) (Aurones). The structural elucidation of compound were done on the basis of analytical and spectral data.